Optimising MIG weld bead geometry of hot rolled carbon steel using response surface method - Junita, Mohd Said; Faiz, Mohd Turan (Springer, Singapore, 2022)
This paper presents the optimisation of weld bead geometry, through Metal Inert Gas butt-welding. Many failures occur in joints due to the bad quality of welding, influenced by a range of parameters across the welding process. With the rapid advancement of computer and automated technologies, new statistical methods for modelling and optimising have been developed. These have eliminated the need for performing experiments on the basis of conventional trial and error, for performance and quality. Experimental methods were set by selecting process parameters, which include the welding current, arc voltage and welding speed and employing a central composite design of Response Surface Methodology method. These methods were adopted as the statistical design of experimental techniques to analyse the performance of the weld bead geometry, i.e. bead height, bead width and penetration, in order to expound the numerical expression between the welding process parameters and the output variable. The results obtained from developing these models indicate that the model predicts weld bead geometry adequately. The effectiveness of process parameters can be estimated by applying the developed mathematical models to a given bead geometry, indicating the change of parameters influences the bead height and width more significantly than penetration alone.